Classroom-Based Management Approaches and Their Perceived Level of Effectiveness - Borlagdan, Rosiely (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the classroom-based management approaches and their perceived effectiveness among public elementary school teachers and school heads in Libon East District, Schools Division of Albay during School Year 2025–2026. Anchored on Assertive Discipline Theory, Classroom Management Theory, Self-Efficacy Theory, and the Positive Learning Environment Theory, the study examined classroom-based management approaches in terms of opening the classroom door, redesigning classroom approaches, enhancing and personalizing professional development, curriculum enrichment and adjustment programs, and classroom and school-wide approaches. A descriptive-evaluative research design was employed. Data were collected using a researcher-made questionnaire supplemented by documentary analysis, interviews, library research, and internet-based sources. The respondents consisted of 50 public elementary school teachers and 22 school heads selected through stratified random sampling. The findings revealed that most teachers were female, within their prime working age, had earned master’s degree units, attended relevant professional trainings, possessed considerable teaching experience, and obtained satisfactory to very satisfactory performance ratings. Classroom-based management approaches were generally perceived as effective, with enhancing and personalizing professional development receiving the highest rating. Significant relationships were found between perceived effectiveness and teachers’ highest educational attainment, relevant trainings attended, length of service, and performance rating, while age and sex showed no significant relationship. There was likewise no significant difference between the perceptions of teachers and school heads regarding the effectiveness of classroom-based management approaches. Based on the findings, intervention activities were developed to further strengthen classroom-based management practices. This study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting effective classroom management practices that enhance teaching and learning processes and foster inclusive and supportive learning environments. It also aligns with SDG 16: Peace, Justice and Strong Institutions through the promotion of safe, orderly, and positive school environments. The study contributes to educational and institutional sustainability by supporting continuous professional development, effective instructional practices, and improved school management systems that promote long-term learner success.